Digital Revolution, Cyber-Crimes And Cyber Legislation: A Challenge To Governments In Developing Countries - Kundi, Ghulam Muhammad (2014)
Cyber-crimes the off-spring of cyber-space technology could be only monitored; controlled and prevented through cyber-legislation. Countries around the globe are facing the dangers of cyber-crimes due to several reasons ranging from the poor technology, incapacity and absence of legislation to financial constraints, lack of cooperation with international law and enforcing agencies. This study was undertaken to asses and analyzes the present state of cyber-crimes and legislation in the perspective of developing countries and to identify and analyze the challenges the governments of developing countries are facing in prevention of the cyber-crimes in general and focusing Pakistan being developing economy in particular and to suggest way-out. This qualitative study used ATLAS.ti software for data analyses. Hermeneutics, discourse and heuristic methods were employed to analyze the qualitative data. Experts suggested the use of different approaches for cyber-legislation for example the minimalist approach and prescriptive approach. However, this study proposes the use of two-tier approach for cyber-legislation against the cyber-crimes in developing countries and Pakistan. Key Words: Cyber-space, Cyber-crimes, Cyber-laws, Minimalist approach, Prescriptive approach, Two-Tier approach